Entrepreneurship in the East German transition process: Lessons for the Korean Peninsula - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2016)
This paper summarizes the role of entrepreneurship in the East German transformation process that followed the breakdown of the socialist regime and subsequent unification with West Germany. The main aim of this exercise is to derive conclusions and recommendations for a potential unification of the Korean Peninsula. We demonstrate that the formation of new businesses played a significant role, while efforts to adapt formerly state-owned firms were much less successful. In East Germany, newly emerging firms created the major share of employment opportunities, while incumbent socialist firms shed vast amounts of labor or disappeared completely. The main implication for a potential unification of the Korean Peninsula is that policy should have a special focus on entrepreneurship. In particular, it should try to utilize and strengthen the entrepreneurial abilities of the North Korean population and to create favorable conditions for the emergence of prospering new businesses.
Keywords: P27; L26; P31; N14; O10; O43; O57; 330; East Germany; entrepreneurship; Korea; transformation